Efficacy of exapar in induction of uterine contraction in vitro and expulsion offetal membranes in buffaloes - GAUTAM, R P; TIWARl, R P; KOLEY, K M; HORE, S K (The Indian Journal of Animal Reproduction, 2023)
Efficacy of exapar (a polyherbal product) was evaluated in inducing uterine muscle contraction in vitro and in prevention and treatment of retention of fetal membranes (RFM) in buffa loes. In experiment I, pieces of estrus goat uterine tissues obtained from slaughter house were exposed to exapar liquid in isolated tissue bath with continuous aeration. A tension of I gm weight was put to the tissue and the response of the ti ssues to exapar was recorded using a student Kymograph. In experiment 2, exapar liquid was orally admi nistered to bu ffaloes just after calving to observe the effect of exapar on the time of expulsion of fetal membranes and reproductive performance. In experiment 3, exapar liquid was administered orally to buffaloes for the treatment of retained fetal membranes. In experiment I, exapar was found to induce a dose-dependent contractile response on isolated estrous goat uterus. Experiment 2 showed significantly earlier expulsion of fetal membranes (4.88±0.51 Vs 7.33±0.74 hr, P < 0.05) and earlier involution of uterus (43 .29±2.41 Vs 49.00±2.20) but no effect on the time required for appearance of first post-partum estrus in exapar treated group than in control group. In experiment 3, no significant differences were observed in the time required for expulsion of fetal membranes and onset of first post partum estrus in exapar treated group than in control group.